Effect of NADPH oxidase inhibitor-apocynin on the expression of Src homology-2 domain-containing phosphatase-1 (SHP-1) exposed renal ischemia/reperfusion injury in rats - Zhiming Li; Yumei Wang (Toxicology Reports, 2015)
This study was designed to evaluate whether NADPH oxidase inhibitor (apocynin) preconditioning induces expression of Src homology-2 domain-containing phosphatase-1 (SHP-1) to protect against renal ischemia/reperfusion (I/R) injury (RI/RI) in rats. Rats were pretreated with 50 mg/kg apocynin, then subjected to 45 min ischemia and 24 h reperfusion. The results indicated that apocynin preconditioning improved the recovery of renal function and nitroso-redox balance, reduced oxidative stress injury and inflammation damage, and upregulated expression of SHP-1 as compared to RI/RI group. Therefore our study demonstrated that apocynin preconditioning provided a protection to the kidney against I/R injury in rats partially through inducing expression of SHP-1.